2013
DOI: 10.1155/2013/741269
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Biological Studies of Binuclear Copper(II) Complexes of (2E)-2-(2-Hydroxy-3-Methoxybenzylidene)-4N-Substituted Hydrazinecarbothioamides

Abstract: Four novel binuclear copper(II) complexes [1-4] of (2E)-2-(2-hydroxy-3-methoxybenzylidene)-4 N-substituted hydrazinecarbothioamides, (OH)(OCH 3 )C 6 H 4 CH=NNHC(S)NHR, where R = H (L 1 ), Me (L 2 ), Et (L 3 ), or Ph (L 4 ), have been synthesized and characterized. The FT-IR spectral data suggested the attachment of copper(II) ion to ligand moiety through the azomethine nitrogen, thioketonic sulphur, and phenolic-O. The spectroscopic characterization indicates the dissociation of dimeric complex into mononuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In this regard, it has been found that some thiosemicarbazones have potent anticancer activity [4][5][6][7][8][9][10][11][12][13][14] The use of iron chelators containing thiosemicarbazones has also been extensively studied [15][16][17][18][19][20][21][22][23][24][25][26] as has the anticancer activity of novel thiosemicarbazones generated through the combination of retro fragments. Some thiosemicarbazones have been found to have antibacterial and antifungal activity [27][28][29] and the pharmacological profile of thiosemicarbazones attached to a heterocyclic core has been reported by Singhal et al [30] The biological profile exhibited by these thiosemicarbazone and semicarbazone derivatives has led to work in which these compounds have been complexed with positron emitting isotopes (e.g. 64 Cu, 68 Ga) for use as imaging agents.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…In this regard, it has been found that some thiosemicarbazones have potent anticancer activity [4][5][6][7][8][9][10][11][12][13][14] The use of iron chelators containing thiosemicarbazones has also been extensively studied [15][16][17][18][19][20][21][22][23][24][25][26] as has the anticancer activity of novel thiosemicarbazones generated through the combination of retro fragments. Some thiosemicarbazones have been found to have antibacterial and antifungal activity [27][28][29] and the pharmacological profile of thiosemicarbazones attached to a heterocyclic core has been reported by Singhal et al [30] The biological profile exhibited by these thiosemicarbazone and semicarbazone derivatives has led to work in which these compounds have been complexed with positron emitting isotopes (e.g. 64 Cu, 68 Ga) for use as imaging agents.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…From this perspective, the synthesis of new metal complexes and evaluation of their antibacterial activity have been considered by the global community as part of the solution (Saha et al, 2009;Rafique et al, 2010). Based on this, a good number of mononuclear (Ghatole et al, 2012;Pasdar et al, 2015;Atakilt Abebe and Tizazu Hailemariam, 2016;Atakilt Abebe and Getinet Tamiru, 2018), binuclear (Patel et al, 2009;Krishna et al, 2013;Gurumoorthy et al, 2014;Panda et al, 2015;) and metal mixed-ligand complexes have been reported in the literature. In particular, Co (II) containing mixed ligand complexes appeared promising in solving the aforementioned problems (Patel et al, 2009;Chang et al, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…The calculated frequencies were employed to assign prominent peaks with maximum accuracy, which resulted in excellent correlation with experimental data ( Figure S1). In the spectra of 1 and 2, the v(OH) was not observed, which suggested that the v(OH) band overlapped with the v(N-H) band due to hydrogen bonding (NH...OH) between the two groups [57,58]. The v (OH) was observed in the calculated spectra because they were generated from the gas phase structures, while experimental spectra were analyzed in the solid state where the compounds are in a more concentrated form, resulting in either intermolecular and/or intramolecular hydrogen bonding similar to that observed in structurally-related Schiff bases [23,59,60].…”
Section: Ftir Analysismentioning
confidence: 98%